Optimizing problem-based learning in civil and electrical engineering: An in-depth study - A.M.N. Kashyap; S.V. Sailaja; B.Murali Krishna; T. Vamseekiran (Journal of Advanced Sciences and Mathematics Education, 2023)
Activity-oriented learning (AOL) is a fundamental aspect of the process of teaching and learning in order to acquire graduate attributes in the field of engineering education. Problem-based learning (PBL) is one such type that enables the acquisition of the desired attributes. The present study furnishes the crafting of legitimate PBL problems in the field of civil and electrical engineering. The problems that are considered can be of various durations and can be classified into different phases depending on the knowledge that is gained by the learners and the requirements of the problems. The augmentation of one phase of a PBL problem that is considered in this study is promising by showing the skill improvement within the learners in solving the real-time problems. The study concluded that with the augmentation of PBL learning, the skills of the engineering learners were enhanced, and the inclusion of PBL in the engineering curriculum can significantly influence the capacities of both the educators and the learners.